Adeno-Associated Virus Vector Mediated Delivery of the HBV Genome Induces Chronic Hepatitis B Virus Infection and Liver Fibrosis in Mice - Ye, Lei; Yu, Haisheng; Li, Chengwen; Hirsch, Matthew L.; Zhang, Liguo; Samulski, R. Jude; Li, Wuping; Liu, Zhong (PLOS ONE, 2015)
Liver cirrhosis and hepatocellular carcinomas are major health problems of chronic hepatitis B virus (HBV) infection. To date, rare model has reproduced liver fibrosis associated with long-term HBV infection which in turn has hindered both the understanding of HBV biology and the development of new treatment options. Here, using adeno-associated virus serotype 8 (AAV8) mediated delivery of a 1.2-kb HBV genome, we successfully generated a chronic HBV infectious mouse model that presents the associated liver fibrosis observed following human infection. After AAV8/HBV1.2 vector administration, mice demonstrated effective HBV replication and transcription which resulted in HBV antigen expression and viremia over 6 months. Although no obvious acute inflammatory response was noted, these mice still developed chronic liver disease and hepatic fibrogenesis as demonstrated by increased ground glass-like hepatocytes, an increasing trend of collagen deposition and upregulated fibrosis markers, including type I collagen, type III collagen, tissue inhibitor of metalloproteinase (TIMP), and transforming growth factor-β1(TGF-β1). Taken together, AAV-mediated HBV gene delivery to the mouse liver, induced HBV persistent infection accompanied by liver fibrosis which can serve as a model for investigating the precise mechanisms underlying liver fibrosis following chronic HBV infection as well as for the potential development of novel therapeutics.